8-Hydroxy-2-methylquinolinium dibromido(2-methylquinolin-8-olato-kappa N-2, O)zincate(II) methanol monosolvate - Najafi, E.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The anion of the title salt, (C10H10NO)[ZnBr2(C10H8NO)]center dot-CH3OH, has its metal atom N,O-chelated by the deprotonated 2-methyl-8-hydroxyquinoline ligand. The hydroxy unit of the cation is a hydrogen-bond donor to the alkoxide O atom of the tetrahedrally coordinated anion, whereas the ammonium cation is a hydrogen-bond donor to the methanolic O atom. In the crystal, adjacent ion pairs and solvent molecules are linked by a methanol-halogen O-H center dot center dot center dot Br hydrogen bond, generating a chain running along the a axis.